Ionic polymer as well as preparation method and application thereof
By introducing a phenyl side chain containing substituents on the main chain of the perfluorostructure, the chemical stability and creep resistance of the sulfonimide-type ionic polymer are improved, and the perfluorosulfonic acid resin in the prior art is solved The problem of water loss at high temperatures has achieved better electrochemical performance and application adaptability.
Patent Information
- Application Number
- CN202411533080.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2024-12-31
AI Technical Summary
The existing perfluorosulfonic acid resin proton exchange membranes lose water at high temperatures lead to a decrease in electrochemical performance, and the phenyl structure of sulfonimide-type ionic polymers is insufficient, which affects its application.
Using the perfluorostructured main chain and substituent-containing phenyl group as side chain end groups, high steric hindrance or high electronegative ionic polymers are prepared through nucleophilic substitution reactions to improve their chemical stability and creep resistance. Reduce production costs through mild reaction conditions and simple separation processes.
It improves the chemical stability and creep resistance of ionic polymers, enhances its electrochemical performance at high temperatures, and is suitable for applications such as fuel cells, water electrolytics and flow batteries.
Smart Images

Figure CN119219810A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to an ionic polymer and a preparation method and application thereof. Background Art
[0002] Perfluorosulfonic acid resin and its membrane materials have been widely used in fuel cell proton exchange membranes and membrane electrodes, chlor-alkali industrial diaphragms, flow battery diaphragms, water electrolysis hydrogen production proton exchange membranes and other fields. Taking fuel cells as an example, the common operating temperature of perfluorosulfonic acid resin proton exchange membranes is 60-80°C. If the operating temperature is further increased, the proton exchange membrane will lose water at high temperature, resulting in a decrease in electrochemical performance, thereby reducing the output power of the fuel cell. Therefore, one direction for improving perfluorosulfonic acid resin proton exchange membranes is to increase their operating temperature range. Sulfonyl imide functional groups have excellent gas-phase acidity, and sulfonyl imide-type ion polymers have the advantages of good thermal stability and strong proton transfer capacity. Compared with sulfonic acid-type ion polymers, they have better electrochemical properties at high temperatures.
[0003] The prior art prepares sulfonyl imide type ionomers by two methods: monomer copolymerization and graft modification. The advantage of the ionomers obtained by monomer copolymerization is that the product structure is clear, but the synthesis conditions are harsh, the reactivity rate of the strongly acidic comonomer is low, and the reaction system is severely corrosive. The terminal group of the side chain of the sulfonyl imide type polymer obtained by graft modification is phenyl, and the oxidation stability of this phenyl structure needs to be further improved. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, an embodiment of the present invention provides an ionic polymer, the main chain of the ionic polymer is a perfluorinated structure, the terminal group of the side chain is a phenyl group containing a substituent, and the high steric hindrance substituent or the high electronegativity substituent improves the chemical stability of the terminal group.
[0005] The ionic polymer of the embodiment of the present invention has a structural formula as shown in formula (1):
[0006]
[0007] In formula (1), a=a positive integer of 0 to 6, b=a positive integer of 2 to 5, x=2 to 10, y=1 to 10000, z×100%≥0.1%;
[0008] M is hydrogen, lithium, sodium, potassium, rubidium, cesium or other cations, wherein the other cations include at least one of ammonium ion, alkaline earth metal ion, iron ion, vanadium ion, titanium ion, silver ion, cerium ion, zinc ion and manganese ion;
[0009] R0 is selected from at least one of -OM, -F, -Cl, -Br, -I;
[0010] R1 is selected from alkylene, fluoroalkylene or direct bond;
[0011] R2, R3, R4, R5 and R6 are each independently selected from at least one of H, alkyl, cycloalkyl, fluoroalkyl, alkylene, phenyl, phenylene, F, and nitrile, and at least one of them is not H.
[0012] The advantages and technical effects brought by the ionic polymer of the embodiment of the present invention are as follows: 1. In the embodiment of the present invention, the main chain of the ionic polymer is a perfluorinated structure, and the end group of the side chain is a phenyl group containing a substituent, and the high steric hindrance substituent or the high electronegativity substituent improves the chemical stability of the end group; 2. In the embodiment of the present invention, using a substituted phenyl group as the end group of the ionic polymer can improve the rigidity and modulus of the ionic polymer and have better creep resistance.
[0013] In some embodiments, the ionic polymer has an EW of 450 to 2000 g / mol.
[0014] In some embodiments, the terminal structure in formula (1) At least one selected from the following structures:
[0015]
[0016] The present invention also provides a method for preparing an ionic polymer, comprising the following steps:
[0017] (1) swelling a sulfonyl halide resin in a first organic medium;
[0018] (2) dispersing a functionalizing agent in a second organic medium to obtain a functionalizing agent solution;
[0019] (3) mixing the swollen sulfonyl halide resin obtained in step (1) and the functionalizing agent solution obtained in step (2), adding an organic base to form a reaction solution, and performing a nucleophilic substitution reaction to obtain a crude ionic polymer product;
[0020] (4) washing the crude ion polymer product obtained in step (3) with a third organic medium, adding the crude product solid to an acid solution for acidification to obtain a crude product solid, washing the crude product solid with water and / or a fourth organic medium, and then dispersing the crude product solid in water and / or a fifth organic medium and filtering to obtain an ion polymer solution;
[0021] (5) drying the ionic polymer solution obtained in step (4) to obtain an ionic polymer solid; or, pouring the ionic polymer solution obtained in step (4) into a poor solvent for precipitation, and drying to obtain an ionic polymer solid.
[0022] The advantages and technical effects brought by the preparation method of the embodiment of the present invention are as follows: 1. In the method of the embodiment of the present invention, the reaction process can be carried out under normal pressure or in a pressure vessel, and the reaction conditions are mild. Even under normal pressure and air atmosphere, the grafting degree of the product is relatively high, and the reaction efficiency is high with less waste of reactants. 2. In the method of the embodiment of the present invention, after the reaction is completed, the polymer product is in a swollen state in the reaction system, and the reaction liquid and the solid product can be directly filtered to separate. The separation process is relatively simple, and the separated liquid can be recycled for related reactions of other batches, which can reduce the generation of organic waste liquid, improve the utilization rate of solvents, functionalizing agents and organic bases, and reduce production costs.
[0023] In some embodiments, in step (1), the first organic medium comprises at least one of acetonitrile, toluene, xylene, carbitol, dioxane, cyclohexane, hexafluorobenzene, decafluorobiphenyl, hexafluoropropylene trimer, pentafluorophenol, perfluoromethyldecahydronaphthalene or tetrahydrofuran;
[0024] And / or, in the step (1), the mass ratio of the sulfonyl halide resin to the first organic medium is 1:3-30.
[0025] In some embodiments, in step (2), the functionalizing agent includes a sulfonamide compound, and the sulfonamide compound includes 2-fluorobenzenesulfonamide, 3-fluorobenzenesulfonamide, 4-fluorobenzenesulfonamide, 2,3-difluorobenzenesulfonamide, 2,4-difluorobenzenesulfonamide, 2,5-difluorobenzenesulfonamide, 2,6-difluorobenzenesulfonamide, 3,4-difluorobenzenesulfonamide, 3,5-difluorobenzenesulfonamide, 2,3,4-trifluorobenzenesulfonamide, 2,3,5-trifluorobenzenesulfonamide, 2,4,5-trifluorobenzenesulfonamide, 2,3,6-trifluorobenzenesulfonamide, 2,4,6-trifluorobenzenesulfonamide, 3,4,5-trifluorobenzenesulfonamide, 2,3,5,6-tetrafluorobenzenesulfonamide, pentafluorobenzenesulfonamide, 2-(trifluoromethyl)benzenesulfonamide, 3-(trifluoromethyl)benzenesulfonamide, 4-(trifluoromethyl)benzenesulfonamide, 2,5-bis(trifluoromethyl)benzenesulfonamide, 3,5-bis(trifluoromethyl)benzenesulfonamide, o-methylbenzenesulfonamide, m-methylbenzenesulfonamide, p-methylbenzenesulfonamide, 2,6-dimethylbenzenesulfonamide, 3,5-dimethylbenzenesulfonamide, 2,4,6-trimethylbenzenesulfonamide, 3,4,5 -trimethylbenzenesulfonamide, 2,3,5,6-tetramethylbenzenesulfonamide, 4-ethylbenzenesulfonamide, 4-propylbenzenesulfonamide, 4-tert-butylbenzenesulfonamide, 2,4,6-triisopropylbenzenesulfonamide, naphthalene-2-sulfonamide, 4-methyl-1-naphthalenesulfonamide, 5,6,7,8-tetrahydro-2-naphthalenesulfonamide, 4-biphenylsulfonamide, biphenyl-2-sulfonamide, 4′-fluorobiphenyl-4-sulfonamide, 2-cyanobenzenesulfonamide, 4-cyanobenzenesulfonamide, 2-fluoro-3-methylbenzenesulfonamide, 2-fluoro-4-methylbenzenesulfonamide, 2-fluoro-5- At least one of methylbenzenesulfonamide, 2-fluoro-5-cyanobenzenesulfonamide, 3-cyano-4-fluorobenzenesulfonamide, 4-fluoro-3-(trifluoromethyl)benzenesulfonamide, 4-fluoro-2-(trifluoromethyl)benzenesulfonamide, 2-fluoro-5-(trifluoromethyl)benzenesulfonamide, o-trifluoromethylbenzylsulfonamide, 3-(trifluoromethyl)benzylsulfonamide, 4-methylbenzylsulfonamide, 2-(1-naphthyl)ethanesulfonamide, (3-methylphenyl)methanesulfonamide, 4-fluorophenylmethanesulfonamide, (3,5-difluorophenyl)methanesulfonamide, and 2-phenyl-ethanesulfonamide;
[0026] And / or, the second organic medium includes at least one of acetonitrile, cyclohexane, toluene, xylene, carbitol, dioxane, DMSO, DMF, DMAc, tetramethylene sulfoxide, hexamethylphosphoramide, N-methylpyrrolidone or tetrahydrofuran.
[0027] In some embodiments, in step (3), the organic base includes at least one of an organic amine containing no nitrogen heterocycle and a nitrogen heterocyclic compound; the organic amine containing no nitrogen heterocycle includes C1-C 20 Alkyl and / or C6~C 20At least one of the organic amines containing no nitrogen heterocyclic ring substituted with an aromatic group; the nitrogen heterocyclic compound includes C1 to C 20 Alkyl and / or C6~C 20 At least one of pyridine, imidazole, pyrrole, piperidine or piperazine substituted with an aromatic group;
[0028] And / or, in the step (3), the mass ratio of the sulfonyl halide resin, the functionalizing agent, and the organic base in the reaction solution is 100:1-400:1-600;
[0029] And / or, in the step (3), the temperature of the nucleophilic substitution reaction is 50 to 180° C., the pressure of the nucleophilic substitution reaction is 0.1 to 10 MPa, and the time of the nucleophilic substitution reaction is 1 to 120 h.
[0030] In some embodiments, in step (4), the third organic medium comprises at least one of aliphatic alcohols, lipids, fatty acids, ketones, tetrahydrofuran, cyclohexane, aromatic hydrocarbons or halogenated hydrocarbons;
[0031] And / or, in step (4), the acid solution comprises at least one of a sulfuric acid solution, a nitric acid solution, a phosphoric acid solution or a hydrochloric acid solution;
[0032] And / or, in the step (4), the temperature of the acidification treatment is 20 to 100° C., and the time of the acidification treatment is 1 to 48 hours;
[0033] and / or, in step (4), the fourth organic medium comprises at least one of fatty alcohols, lipids, fatty acids, ketones or tetrahydrofuran;
[0034] And / or, in the step (4), the fifth organic medium comprises at least one of aliphatic alcohol, fatty acid, ethylene glycol, propylene glycol, glycerol, DMF, DMSO, DMAc, tetramethylene sulfoxide, tetrahydrofuran, hexamethylphosphoramide, and NMP;
[0035] And / or, in step (4), the solid content of the ionic polymer solution is 0.5% to 40%.
[0036] In some embodiments, in step (5), the drying process is freeze drying, forced air drying or vacuum drying;
[0037] And / or, in step (5), the volume of the poor solvent is 2 to 5 times that of the ionic polymer solution;
[0038] And / or, in step (5), the poor solvent includes at least one of lipids, aromatic hydrocarbons, alkanes, ketones, and halogenated hydrocarbons.
[0039] The embodiments of the present invention also provide the use of the above-mentioned ionic polymer or the ionic polymer prepared by the above-mentioned preparation method in an ion exchange membrane.
[0040] The embodiment of the present invention further provides an ion exchange membrane, comprising the above-mentioned ionic polymer or the ionic polymer prepared by the above-mentioned preparation method.
[0041] The ion exchange membrane of the embodiment of the present invention has the above-mentioned ion polymer. The sulfonimide functional group of the ion polymer has the strongest gas-phase acidity, which improves the ion transmission capacity of the material at high temperature and can improve the proton conductivity of the ion exchange membrane, making it suitable for fuel cell ion exchange membranes, ion exchange membranes for water electrolysis and liquid flow battery diaphragms.
[0042] In some embodiments, the ion exchange membrane further comprises a reinforcement membrane.
[0043] The embodiments of the present invention also provide applications of the above-mentioned ion exchange membrane in batteries, chlor-alkali industry, water electrolysis to produce hydrogen, capacitors, electrodialysis, sensors, desalination membranes, ultrafiltration membranes, microfiltration membranes, fabrics, and protective equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 are the infrared spectra of PEM-9, PEM-10, and D-PEM-14F;
[0045] Figure 2 are cross-sectional SEM images of PEM-15 and D-PEM-15;
[0046] Figure 3 It is the polarization curve diagram of PEM-15 and D-PEM-15. DETAILED DESCRIPTION
[0047] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0048] The ionic polymer of the embodiment of the present invention has a structural formula as shown in formula (1):
[0049]
[0050] In formula (1), a=a positive integer of 0 to 6, b=a positive integer of 2 to 5, x=2 to 10, y=1 to 10000, z×100%≥0.1%;
[0051] M is hydrogen, lithium, sodium, potassium, rubidium, cesium or other cations, wherein the other cations include at least one of ammonium ion, alkaline earth metal ion, iron ion, vanadium ion, titanium ion, silver ion, cerium ion, zinc ion and manganese ion;
[0052] R0 is selected from at least one of -OM, -F, -Cl, -Br, -I;
[0053] R1 is selected from alkylene, fluoroalkylene or direct bond;
[0054] R2, R3, R4, R5 and R6 are each independently selected from at least one of H, alkyl, cycloalkyl, fluoroalkyl, alkylene, phenyl, phenylene, F, and nitrile, and at least one of them is not H.
[0055] The main chain of the ionic polymer of the embodiment of the present invention is a perfluorinated structure, and the end group of the side chain is a phenyl group containing a substituent. The high steric hindrance substituent or the high electronegativity substituent improves the chemical stability of the end group; using the substituted phenyl group as the end group of the ionic polymer can improve the rigidity and modulus of the ionic polymer and have better creep resistance.
[0056] In some embodiments, preferably, the R0 is selected from at least one of -OLi, -ONa, -OK, -OH, and -F, more preferably -OH.
[0057] In some embodiments, preferably, the R1 is selected from at least one of methylene, ethylene, propylene, butylene, perfluoromethylene, perfluoroethylene, CH(CH3) or a direct bond, more preferably methylene or a direct bond.
[0058] In some embodiments, preferably, R2, R3, R4, R5 and R6 are each independently selected from at least one of H, methyl, ethyl, n-propyl, cyclohexyl, isopropyl, n-butyl, tert-butyl, phenylene, phenyl, 4-fluorophenyl, 4-methylphenyl, trifluoromethyl, pentafluoroethyl or F, and at least one is not H. More preferably, R2, R3, R4, R5 and R6 are each independently selected from at least one of methyl, isopropyl, tert-butyl, phenyl, trifluoromethyl or F. Further preferably, R2, R3, R4, R5 and R6 are each independently selected from at least one of trifluoromethyl or F.
[0059] In some embodiments, preferably, the EW of the ionic polymer is 450 to 2000 g / mol. More preferably, the EW of the ionic polymer is 600 to 1500 g / mol. Further preferably, the EW of the ionic polymer is 700 to 1200 g / mol. In the embodiment of the present invention, the value of EW is optimized so that the ionic polymer has a higher ion exchange capacity and stable water absorption and swelling performance; if the EW value is too high, the ion exchange capacity (IEC) of the material is low, the ion exchange capacity and ion transport capacity are poor, and when used in a proton exchange membrane or a membrane electrode, its electrochemical performance will be poor; if the EW value is too low, the water absorption and swelling of the material is difficult to control, and excessive water absorption and swelling will sharply reduce the dimensional stability and mechanical properties of the material.
[0060] In some embodiments, preferably, x=3-8, and more preferably 4-7.
[0061] In some embodiments, preferably, y=10-5000, and more preferably 100-2000.
[0062] x and z determine the ion exchange equivalent (EW) of the polymer, y determines the molecular weight of the polymer, z×100% is the grafting rate of the sulfonyl imide group, and the higher the grafting rate, the higher the proportion of the side chains containing the sulfonyl imide group. Preferably, the grafting rate of the ionic polymer is ≥0.1%. More preferably, the grafting rate of the ionic polymer is ≥10%; further preferably, the grafting rate of the ionic polymer is ≥50%.
[0063] In some embodiments, preferably, the terminal structure in formula (1) At least one selected from the following structures:
[0064]
[0065] In the embodiment of the present invention, the substituent structure of phenyl is preferred, among which isopropyl, phenyl and tert-butyl have large steric hindrance and can improve the free radical resistance of the side chain end group of the ionic polymer; F and trifluoromethyl as substituents of the benzene ring can improve the chemical stability, mechanical strength and electrochemical properties of the ionic polymer.
[0066] More preferably, at least one of 3-fluorophenyl, 4-fluorophenyl, 3,5-difluorophenyl, 2,6-difluorophenyl, 2,5-difluorophenyl, 2-(trifluoromethyl)phenyl, 2-fluoro-5-(trifluoromethyl)phenyl, 3-(trifluoromethyl)phenyl, 4-(trifluoromethyl)phenyl, 3,5-bis(trifluoromethyl)phenyl, 2,5-bis(trifluoromethyl)phenyl, 2,3,4,5,6-pentafluorophenyl, 2,4,6-trifluorophenyl or 2,3,5,6-tetrafluorophenyl is preferred. Further preferably, at least one of 4-fluorophenyl, 4-(trifluoromethyl)benzene or 2,3,4,5,6-pentafluorophenyl is preferred. Fluorine-containing substituents can significantly improve the chemical stability of ionic polymers. In terms of the positional distribution of substituents, symmetrical end groups have better chemical stability.
[0067] The method for preparing the ionic polymer according to the embodiment of the present invention comprises the following steps:
[0068] (1) swelling a sulfonyl halide resin in a first organic medium;
[0069] (2) dispersing a functionalizing agent in a second organic medium to obtain a functionalizing agent solution;
[0070] (3) mixing the swollen sulfonyl halide resin obtained in step (1) and the functionalizing agent solution obtained in step (2), adding an organic base to form a reaction solution, and performing a nucleophilic substitution reaction to obtain a crude ionic polymer product;
[0071] (4) washing the crude ion polymer product obtained in step (3) with a third organic medium, adding the crude product solid to an acid solution for acidification to obtain a crude product solid, washing the crude product solid with water and / or a fourth organic medium, and then dispersing the crude product solid in water and / or a fifth organic medium and filtering to obtain an ion polymer solution;
[0072] (5) drying the ionic polymer solution obtained in step (4) to obtain an ionic polymer solid; or, pouring the ionic polymer solution obtained in step (4) into a poor solvent for precipitation, and drying to obtain an ionic polymer solid.
[0073] According to the preparation method of the embodiment of the present invention, the reaction process can be carried out under normal pressure or in a pressure vessel, the reaction conditions are mild, and the grafting degree of the product is high even under normal pressure and air atmosphere, and the reaction efficiency is high with less waste of reactants; according to the method of the embodiment of the present invention, after the reaction is completed, the polymer product is in a swollen state in the reaction system, and the reaction liquid and the solid product can be directly filtered to separate, the separation process is relatively simple, and the separated liquid can be recycled for related reactions of other batches, which can reduce the generation of organic waste liquid, improve the utilization rate of solvents, functionalization reagents and organic bases, and reduce production costs.
[0074] The synthetic route of ionic polymer is shown in formula (2):
[0075]
[0076] In formula (2), a, b, x, y, R1, R2, R3, R4, R5 and R6 are the same as those in formula (1), and X is F, Cl, Br or I, preferably F or Cl, and more preferably F. Sulfonyl fluoride compounds and sulfonyl chloride compounds have high reactivity with sulfonamide resins, but the sulfonyl chloride group is easily deliquescent and needs to be stored and reacted under anhydrous conditions, which places higher requirements on the reaction system, so sulfonyl fluoride resin is the most preferred raw material.
[0077] In some embodiments, preferably, in the step (1), the first organic medium includes at least one of acetonitrile, toluene, xylene, carbitol, dioxane, cyclohexane, hexafluorobenzene, decafluorobiphenyl, hexafluoropropylene trimer, pentafluorophenol, perfluoromethyl decahydronaphthalene or tetrahydrofuran. More preferably, the first organic medium includes at least one of acetonitrile, cyclohexane, dioxane, hexafluorobenzene, decafluorobiphenyl or hexafluoropropylene trimer. Further preferably, the first organic medium includes at least one of acetonitrile, cyclohexane, dioxane or hexafluorobenzene. The embodiment of the present invention preferably selects the type of the first organic medium. The solubility of the sulfonyl fluoride resin is extremely poor and it can only swell in some solvents. Selecting a suitable solvent can fully swell the sulfonyl fluoride resin, which is convenient for subsequent reactions.
[0078] In some embodiments, preferably, in the step (1), the mass ratio of the sulfonyl halide resin to the first organic medium is 1:3 to 30. More preferably, the mass ratio of the sulfonyl halide resin to the first organic medium is 1:4 to 25. Further preferably, the mass ratio of the sulfonyl halide resin to the first organic medium is 1:5 to 20. Too little amount of the first organic medium is not conducive to the swelling and dispersion of the sulfonyl halide resin, and too much amount will dilute the concentration of the functionalizing agent and the organic base in the subsequent reaction, which is not conducive to the nucleophilic substitution reaction.
[0079] In some embodiments, preferably, in step (2), the functionalizing agent comprises a sulfonamide compound, and the sulfonamide compound comprises 2-fluorobenzenesulfonamide, 3-fluorobenzenesulfonamide, 4-fluorobenzenesulfonamide, 2,3-difluorobenzenesulfonamide, 2,4-difluorobenzenesulfonamide, 2,5-difluorobenzenesulfonamide, 2,6-difluorobenzenesulfonamide, 3,4-difluorobenzenesulfonamide, 3,5-difluorobenzenesulfonamide, 2,3,4-trifluorobenzenesulfonamide, 2,3,5-trifluorobenzenesulfonamide, 2,4,5-trifluorobenzenesulfonamide, 2,3,6-trifluorobenzenesulfonamide. amide, 2,4,6-trifluorobenzenesulfonamide, 3,4,5-trifluorobenzenesulfonamide, 2,3,5,6-tetrafluorobenzenesulfonamide, pentafluorobenzenesulfonamide, 2-(trifluoromethyl)benzenesulfonamide, 3-(trifluoromethyl)benzenesulfonamide, 4-(trifluoromethyl)benzenesulfonamide, 2,5-bis(trifluoromethyl)benzenesulfonamide, 3,5-bis(trifluoromethyl)benzenesulfonamide, o-methylbenzenesulfonamide, m-methylbenzenesulfonamide, p-methylbenzenesulfonamide, 2,6-dimethylbenzenesulfonamide, 3,5-dimethylbenzenesulfonamide, 2,4,6-trimethylbenzenesulfonamide, 3,4 ,5-trimethylbenzenesulfonamide, 2,3,5,6-tetramethylbenzenesulfonamide, 4-ethylbenzenesulfonamide, 4-propylbenzenesulfonamide, 4-tert-butylbenzenesulfonamide, 2,4,6-triisopropylbenzenesulfonamide, naphthalene-2-sulfonamide, 4-methyl-1-naphthalenesulfonamide, 5,6,7,8-tetrahydro-2-naphthalenesulfonamide, 4-biphenylsulfonamide, biphenyl-2-sulfonamide, 4′-fluorobiphenyl-4-sulfonamide, 2-cyanobenzenesulfonamide, 4-cyanobenzenesulfonamide, 2-fluoro-3-methylbenzenesulfonamide, 2-fluoro-4-methylbenzenesulfonamide, 2-fluoro-5 -methylbenzenesulfonamide, 2-fluoro-5-cyanobenzenesulfonamide, 3-cyano-4-fluorobenzenesulfonamide, 4-fluoro-3-(trifluoromethyl)benzenesulfonamide, 4-fluoro-2-(trifluoromethyl)benzenesulfonamide, 2-fluoro-5-(trifluoromethyl)benzenesulfonamide, o-trifluoromethylbenzylsulfonamide, 3-(trifluoromethyl)benzylsulfonamide, 4-methylbenzylsulfonamide, 2-(1-naphthyl)ethanesulfonamide, (3-methylphenyl)methanesulfonamide, 4-fluorophenylmethanesulfonamide, (3,5-difluorophenyl)methanesulfonamide, and at least one of 2-phenyl-ethanesulfonamide.Further preferably, the sulfonamide compounds include 2-fluorobenzenesulfonamide, 3-fluorobenzenesulfonamide, 4-fluorobenzenesulfonamide, 2,3-difluorobenzenesulfonamide, 2,4-difluorobenzenesulfonamide, 2,5-difluorobenzenesulfonamide, 2,6-difluorobenzenesulfonamide, 3,4-difluorobenzenesulfonamide, 3,5-difluorobenzenesulfonamide, 2,3,4-trifluorobenzenesulfonamide, 2,3,5-trifluorobenzenesulfonamide, 2,3,6-trifluorobenzenesulfonamide, 2,4,6-trifluorobenzenesulfonamide, 3,4,5-trifluorobenzenesulfonamide, At least one of 2,3,5,6-tetrafluorobenzenesulfonamide, pentafluorobenzenesulfonamide, 2-(trifluoromethyl)benzenesulfonamide, 3-(trifluoromethyl)benzenesulfonamide, 4-(trifluoromethyl)benzenesulfonamide, 2,5-bis(trifluoromethyl)benzenesulfonamide, 3,5-bis(trifluoromethyl)benzenesulfonamide, 4-fluoro-3-(trifluoromethyl)benzenesulfonamide, 4-fluoro-2-(trifluoromethyl)benzenesulfonamide, 5-fluoro-2-(trifluoromethyl)benzenesulfonamide, o-trifluoromethylbenzylsulfonamide, 3-(trifluoromethyl)benzylsulfonamide. More preferably, the sulfonamide compound includes at least one of 4-fluorobenzenesulfonamide, 4-(trifluoromethyl)benzenesulfonamide or pentafluorobenzenesulfonamide.
[0080] In some embodiments, preferably, in the step (2), the second organic medium comprises at least one of acetonitrile, cyclohexane, toluene, xylene, carbitol, dioxane, DMSO, DMF, DMAc, tetramethylene sulfoxide, hexamethylphosphoramide, N-methylpyrrolidone (NMP) or tetrahydrofuran. More preferably, the second organic medium comprises at least one of acetonitrile, cyclohexane, toluene, DMSO, DMF or DMAc.
[0081] In some embodiments, preferably, in step (2), the functionalizing agent and the second organic medium can be mixed in any proportion, and preferably, in the functionalizing agent solution, the mass content of the functionalizing agent is 1% to 80%, preferably 10% to 60%, and more preferably 10% to 40%.
[0082] In some embodiments, preferably, in step (3), the organic base includes at least one of an organic amine containing no nitrogen heterocycle and a nitrogen heterocyclic compound; the organic amine containing no nitrogen heterocycle includes C1 to C 20 Alkyl and / or C6~C 20 At least one of the organic amines containing no nitrogen heterocyclic ring substituted with an aromatic group; the nitrogen heterocyclic compound includes C1 to C 20 Alkyl and / or C6~C 20At least one of aryl-substituted pyridine, imidazole, pyrrole, piperidine or piperazine. More preferably, the organic base includes at least one of triethylamine, tripropylamine, triisopropylamine, tributylamine, tripentylamine, trihexylamine, triphenylamine, dodeca-tertiary amine, octadec-tertiary amine, N,N-dimethylcyclohexylamine, N,N-dimethylethylenediamine, N,N-diethylethylenediamine, N,N-dibutylethylenediamine, N,N-dimethylhexylamine, triethylethylenediamine, tetramethylethylenediamine, tetramethyl-1,3-propylenediamine, tetramethyl-1,6-hexanediamine, 2,5-dimethyl-p-phenylenediamine, N,N'-dibutylphenylenediamine, and N,N-dimethyldipropylenetriamine. Further preferably, the organic base includes at least one of triethylamine, tripropylamine or tributylamine.
[0083] In some embodiments, preferably, in step (3), the mass ratio of the sulfonyl halide resin, the functionalizing agent, and the organic base in the reaction solution is 100:1-400:1-600. More preferably, the mass ratio of the sulfonyl halide resin, the functionalizing agent, and the organic base in the reaction solution is 100:10-250:10-500. Further preferably, the mass ratio of the sulfonyl halide resin, the functionalizing agent, and the organic base in the reaction solution is 100:30-200:30-400.
[0084] The first organic medium, the second organic medium and the organic base all have a dispersing effect on the sulfonyl halide resin and the functionalizing agent, the total mass of the first organic medium, the second organic medium and the organic base is m1, and the total mass of the sulfonyl halide resin and the functionalizing agent is m2. m1:m2=100:1-60, preferably 100:3-40, more preferably 100:5-30.
[0085] In some embodiments, preferably, in the step (3), the temperature of the nucleophilic substitution reaction is 50 to 180°C. More preferably, in the step (3), the temperature of the nucleophilic substitution reaction is 60 to 150°C. Further preferably, in the step (3), the temperature of the nucleophilic substitution reaction is 80 to 120°C. The reaction temperature is not higher than the boiling point of each component in the first organic medium, the second organic medium, the functionalizing agent and the organic base mixture, and the reaction system can be reacted at a higher temperature by condensation reflux; the increase in temperature is conducive to accelerating the reaction rate and reducing the reaction time.
[0086] In some embodiments, preferably, in step (3), the temperature of the nucleophilic substitution reaction can be increased by increasing the pressure, and the pressure of the nucleophilic substitution reaction is 0.1 to 10 MPa, such as 0.1 MPa, 1 MPa, 5 MPa, 10 MPa, etc.
[0087] In some embodiments, preferably, in the step (3), the time of the nucleophilic substitution reaction is 1h to 120h. Further preferably, the time of the nucleophilic substitution reaction is 12h to 96h. More preferably, the time of the nucleophilic substitution reaction is 24h to 72h. The reaction rates of the sulfonyl halide resin and the functionalizing agent at different temperatures are different, and sufficient reaction time can improve the degree of reaction. If the reaction time is too short, the degree of reaction is low and the grafting rate of the product is low; if the reaction time is too long, the degree of reaction is basically unchanged, and the grafting rate will not be further improved.
[0088] In some embodiments, preferably, in the step (4), the third organic medium includes at least one of aliphatic alcohols, lipids, fatty acids, ketones, tetrahydrofuran, cyclohexane, aromatic hydrocarbons or halogenated hydrocarbons. More preferably, the third organic medium includes at least one of methanol, ethanol, isopropanol, n-propanol, formic acid, acetic acid, ethyl acetate, acetone, butanone, methyl isobutyl ketone, cyclohexanone, isophorone, diacetone, tetrahydrofuran, toluene, xylene, dichloromethane or chloroform. Further preferably, the third organic medium includes at least one of ethanol, isopropanol, n-propanol, ethyl acetate, acetone or butanone. The preferred third organic medium of the embodiment of the present invention has controllable cost, low toxicity, and is volatile, and has good miscibility with the first organic medium, the second organic medium, the functionalizing agent, and the organic base.
[0089] In some embodiments, preferably, in step (4), the acid solution comprises at least one of a sulfuric acid solution, a nitric acid solution, a phosphoric acid solution or a hydrochloric acid solution. More preferably, the acid solution comprises at least one of a sulfuric acid solution or a hydrochloric acid solution.
[0090] In some embodiments, preferably, in step (4), the concentration of the acid solution is ≥5%; more preferably, the acid concentration is ≥15%; further preferably, the acid concentration is ≥30%. Ionic polymers are hydrophilic, and too low an acid concentration may cause part of the product to dissolve in the acid solution. The common ion effect between a high concentration of the acid solution and the ionic polymer will make it difficult for the ionic polymer to dissolve and be fully acidified.
[0091] In some embodiments, preferably, in the step (4), the temperature of the acidification treatment is 20 to 100°C, specifically, for example, 20°C, 25°C, 30°C, 50°C, 100°C, etc.; and / or the time of the acidification treatment is 1 to 48 hours.
[0092] In some embodiments, preferably, in the step (4), the fourth organic medium comprises at least one of a fatty alcohol, a lipid, a fatty acid, a ketone or tetrahydrofuran. More preferably, the fourth organic medium comprises at least one of methanol, ethanol, isopropanol, n-propanol, formic acid, acetic acid, ethyl acetate, acetone, butanone, methyl isobutyl ketone, cyclohexanone, isophorone, diacetone or tetrahydrofuran. Further preferably, the fourth organic medium comprises at least one of ethanol, isopropanol, n-propanol, acetone or butanone. More preferably, the fourth organic medium comprises at least one of acetone or butanone. Acetone and butanone have controllable costs, are poor solvents for ionic polymers, do not dissolve the product, have good miscibility with hydrochloric acid solution, can efficiently and thoroughly purify the product, and are the most preferred fourth organic medium. Fatty alcohols such as ethanol may dissolve and disperse some low EW ionic polymers, and are generally suitable for ionic polymers with EW≥900g / mol. Water may also dissolve and disperse some low EW ionic polymers, and are generally suitable for ionic polymers with EW≥900g / mol. Mixing water with ketone solvents (acetone, butanone, etc.) can improve the cleaning efficiency of the acid solution. Preferably, the mass content of water in the mixed solvent is less than 30%.
[0093] In some embodiments, preferably, in the step (4), the fifth organic medium includes at least one of aliphatic alcohols, fatty acids, ethylene glycol, propylene glycol, glycerol, DMF, DMSO, DMAc, tetramethylene sulfoxide, tetrahydrofuran, hexamethylphosphoric acid triamide, and NMP. More preferably, the fifth organic medium includes at least one of methanol, ethanol, n-propanol, isopropanol, n-hexanol, formic acid, acetic acid, DMF, DMSO, DMAc, tetrahydrofuran, or NMP. Further preferably, the fifth organic medium includes at least one of ethanol, n-propanol, isopropanol, DMF, DMSO, or DMAc. The fifth organic medium preferred in the embodiment of the present invention can fully dissolve the ionic polymer to form a solution or the mixed medium after mixing with water can fully dissolve the ionic polymer to form a solution. High boiling point solvents such as polyols and NMP can also fully dissolve the ionic polymer, but too high a boiling point makes it difficult to dry the solution. Fatty acids such as formic acid and acetic acid have strong adsorption in ionic polymers, which also increases the difficulty of drying.
[0094] In some embodiments, preferably, in step (4), the solid content of the ionic polymer solution is 0.5% to 40%. More preferably, the solid content of the ionic polymer solution is 2% to 20%. If the solid content is too low, the solvent consumption will be too large, and if the solid content is too high, the solution viscosity will increase, which is not conducive to filtering and removing insoluble impurities.
[0095] In some embodiments, preferably, in step (5), the drying process is freeze drying, forced air drying or vacuum drying.
[0096] In some embodiments, preferably, in step (5), the volume of the poor solvent is 2 to 5 times that of the ionic polymer solution.
[0097] In some embodiments, preferably, in the step (5), the poor solvent includes at least one of lipids, aromatic hydrocarbons, alkanes, ketones, and halogenated hydrocarbons. More preferably, the poor solvent includes at least one of ethyl acetate, toluene, n-hexane, n-pentane, cyclohexane, acetone, butanone, or dichloromethane. Further preferably, the poor solvent includes at least one of n-hexane, cyclohexane, acetone, or butanone. Aromatic hydrocarbons and halogenated hydrocarbons are highly toxic; lipid solvents are easily hydrolyzed into fatty acids and fatty alcohols by the acidic action of fluoropolymers; acetone and butanone have good miscibility with water, and also have good miscibility with the fifth organic medium, and are preferred poor reagents; n-hexane and cyclohexane have poor miscibility with water and highly polar organic solvents, but they have a great difference in polarity with ionic polymers, and have a good precipitation effect. In view of the problem of poor miscibility, ketones, halogenated hydrocarbons, aromatic hydrocarbons, and alkanes can be mixed as poor reagents.
[0098] The embodiments of the present invention also provide the use of the above-mentioned ionic polymer or the ionic polymer prepared by the above-mentioned method in an ion exchange membrane.
[0099] The embodiment of the present invention further provides an ion exchange membrane, comprising the above-mentioned ionic polymer or the ionic polymer prepared by the above-mentioned preparation method.
[0100] The ion exchange membrane of the embodiment of the present invention has the above-mentioned ion polymer. The sulfonimide functional group of the ion polymer has the strongest gas-phase acidity, which improves the ion transmission capacity of the material at high temperature and can improve the proton conductivity of the ion exchange membrane, making it suitable for fuel cell ion exchange membranes, ion exchange membranes for water electrolysis and liquid flow battery diaphragms.
[0101] In some embodiments, preferably, the ion exchange membrane has a thickness of 5 to 450 μm. More preferably, the ion exchange membrane has a thickness of 6 to 300 μm. Further preferably, the ion exchange membrane has a thickness of 7 to 200 μm.
[0102] In some embodiments, preferably, the ion exchange capacity of the ion exchange membrane is 0.1 to 4 mmol / g. More preferably, the ion exchange capacity of the ion exchange membrane is 0.15 to 2.5 mmol / g. Further preferably, the ion exchange capacity of the ion exchange membrane is 0.2 to 2.0 mmol / g.
[0103] In some embodiments, preferably, the ion exchange membrane also includes a reinforced membrane. Further preferably, the reinforced membrane is a porous membrane, and the material of the porous membrane includes at least one of non-fluorinated polyolefins, fluorinated polymer materials and aromatic polymers; the non-fluorinated polyolefins include at least one of polyethylene, polypropylene or ethylene-propylene copolymers; the fluorinated polymer materials include polytetrafluoroethylene, tetrafluoroethylene hexafluoropropylene copolymers, tetrafluoroethylene propylene copolymers, ethylene tetrafluoroethylene copolymers, tetrafluoroethylene hexafluoropropylene ethylene copolymers, polyvinylidene fluoride, vinylidene fluoride hexafluoropropylene copolymers, tetrafluoroethylene perfluoroalkyl vinyl ether copolymers, vinylidene fluoride tetrafluoroethylene hexafluoropropylene copolymers, polyvinyl fluoride, polychlorotrifluoroethylene, ethylene chlorotrifluoroethylene copolymers; the aromatic polymer membrane includes at least one of polyaryletherketone, polysulfone, polyethersulfone, polyethersulfoneketone, polybenzimidazole, polyaromatic amide, polyimide or polyetheretherketone.
[0104] The present invention also provides a method for preparing an ion exchange membrane, comprising the following steps:
[0105] (a) dispersing the above-mentioned ionic polymer or the ionic polymer obtained by the above-mentioned method in a solvent to obtain a resin slurry;
[0106] (b) forming the resin slurry and drying it to obtain an ion exchange membrane.
[0107] The method for preparing an ion exchange membrane provided by an embodiment of the present invention obtains an ion exchange membrane by solution molding and drying. The obtained ion exchange membrane has good flatness, uniform thickness distribution, and better performance; the process is simple, easy to operate, and has high production efficiency, which is convenient for wide application in industrial production; the resin slurry in the preparation process can also be used to prepare coatings, hydrogels and adhesives for porous membranes such as desalination membranes and ultra / microfiltration membranes, as well as various fabrics and protective equipment such as surgical gloves, protective clothing, and sterile sheets, and has a wide range of applications.
[0108] In some embodiments, preferably, in the step (a), the dispersion temperature is 10 to 240°C; and / or the dispersion time is 0.1 to 24 hours; and / or the dispersion pressure is normal pressure (atmospheric pressure) to 20 MPa; and / or the dispersion method includes at least one of stirring, shaking or ultrasound.
[0109] In some embodiments, preferably, in the step (a), the solvent comprises at least one of water, a high boiling point organic solvent, tetrahydrofuran or a lower aliphatic alcohol; the high boiling point organic solvent comprises at least one of ethylene glycol, propylene glycol, glycerol, DMF, DMAC, DMSO, hexamethylphosphoramide or NMP, and the lower aliphatic alcohol comprises at least one of methanol, ethanol, isopropanol, n-propanol or n-butanol.
[0110] In some embodiments, preferably, in the step (b), the forming comprises at least one of casting, pouring or coating.
[0111] In some embodiments, preferably, in the step (b), the drying temperature is 20 to 180°C.
[0112] In some embodiments, preferably, the step (b) further comprises coating the resin slurry on one side or both sides of the reinforcement membrane, and obtaining the ion exchange membrane after drying. More preferably, the coating comprises at least one of dipping, blade coating, and slit coating.
[0113] In some embodiments, preferably, the resin slurry in step (b) can be replaced by the ionic polymer solution in step (4).
[0114] The embodiments of the present invention also provide applications of the above-mentioned ion exchange membrane in batteries, chlor-alkali industry, water electrolysis to produce hydrogen, capacitors, electrodialysis, sensors, desalination membranes, ultrafiltration membranes, microfiltration membranes, fabrics, and protective equipment.
[0115] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and drawings.
[0116] Example 1
[0117] (1) Weighing 1 g of sulfonyl fluoride resin 1 and swelling it in a first organic medium;
[0118] (2) dispersing a certain amount of a functionalizing agent in a certain amount of a second organic medium to obtain a functionalizing agent solution;
[0119] (3) mixing the swollen sulfonyl fluoride resin and the functionalizing agent solution in a flask, then adding a certain amount of organic base dropwise at 20° C., then heating the reaction system to 80° C. and stirring the reaction for 48 hours;
[0120] (4) After the reaction is completed, the solid crude product is washed alternately with acetone and ethyl acetate, and then poured into 37% concentrated hydrochloric acid for acidification at a temperature of 30°C for 24 hours. The acidified solid product is washed with acetone until the pH value of the washing solution reaches 6.5 to 7.5. The washed solid is dissolved in 15 mL of a water-alcohol mixed solvent (the mass ratio of water, ethanol, and isopropanol is 1:1:2), and the insoluble matter is filtered out to obtain an ion polymer solution;
[0121] (5) The ionic polymer solution was poured into 50 mL of cold acetone to obtain an ionic polymer solid precipitate, which was then vacuum dried at 45° C. for 48 h to obtain a clean ionic polymer solid.
[0122] Sulfonyl fluoride resin and functionalizing agent are not sensitive to water and oxygen, all reaction reagents do not need to be strictly dehydrated, and the reaction process does not need nitrogen or other inert gas protection.
[0123] The structural formula of sulfonyl fluoride resin 1 is:
[0124]
[0125] Table 1 shows the types and amounts of the first organic medium, the second organic medium and the organic base.
[0126] Table 2 shows the type and amount of functionalizing agents and the free radical resistance of ionic polymers.
[0127] Table 3 shows the structural formula, EW and grafting rate of the ionic polymers.
[0128] Table 1
[0129] Ionic polymers The first organic medium Second organic medium Organic base PFNA-1 1.57g acetonitrile, 20.96g hexafluorobenzene 11.38gDMF 4.37 g triethylamine PFNA-2 1.74g toluene, 16.12g hexafluorobenzene 3.75g DMAc 2.18 g triethylamine PFNA-3 2.07g dioxane, 12.9g hexafluorobenzene, 5.5g DMSO 4.37 g triethylamine PFNA-4 10.22 g acetonitrile, 1.56 g cyclohexane 7.5g DMAc 4.37 g triethylamine PFNA-5 12.41 g dioxane, 2.34 g cyclohexane 13.12g DMAc 4.37 g triethylamine PFNA-6 12.41 g dioxane 6.98 g toluene 3.01g tripropylamine PFNA-7 16.12g hexafluorobenzene, 1.57g acetonitrile 1.9g DMF 0.78g tributylamine PFNA-8 1.74 g toluene, 13.44 g dioxane 7.5gDMAc 4.37 g triethylamine PFNA-9 2.07g dioxane, 16.12g hexafluorobenzene 4.4 g DMSO 4.37 g triethylamine
[0130] Table 2
[0131]
[0132] Table 3
[0133]
[0134]
[0135] By adding a certain amount of functionalizing agent and organic base, the sulfonyl imide group is grafted through a nucleophilic substitution reaction under certain reaction conditions. A suitable reaction system can make the grafting rate reach more than 90%, and the substituent-containing benzenesulfonamide and sulfonyl fluoride resin have good reactivity. The amount of functionalizing agent added to PFNA-7 is small, and the grafting rate is low.
[0136] Example 2
[0137] (1) 10 g of the sulfonyl fluoride resin 1 in Example 1 was weighed and swelled in a mixed solvent of 161.2 g of hexafluorobenzene and 20.7 g of dioxane. The swelling process was carried out in an autoclave;
[0138] (2) Weigh 14.2 g of 4-fluorobenzenesulfonamide and dissolve it in 28.1 g of DMAc. After it is fully dissolved, pour the functionalization reagent solution into an autoclave and stir to mix;
[0139] (3) Add 14.6 g of triethylamine to the autoclave and stir and mix in the autoclave for 10 min under nitrogen atmosphere. Use a high-pressure nitrogen bottle to pressurize the autoclave to 4 MPa (20°C), raise the temperature to 100°C, the pressure in the autoclave to 5.1 MPa, and stir to react for 12 h. Raise the temperature to 120°C, the pressure in the autoclave to 5.4 MPa, and stir to react for 24 hours. Cool to below 20°C, release the pressure in the autoclave, and pour out the reaction product.
[0140] (4) The solid crude product was washed alternately with butanone and dichloromethane, and then poured into 12.4% concentrated hydrochloric acid for acidification at a temperature of 80°C for 24 hours. The acidified solid product was washed with acetone until the pH value of the washing solution reached 6.5 to 7.5. The washed solid was dissolved in 142.2 g of DMF, and the insoluble matter was removed by filtration to obtain an ionic polymer solution.
[0141] (5) 10 mL of ionic polymer solution was reserved for preparing ion exchange membranes, and the remaining ionic polymer solution was poured into 500 mL of poor solvent (the mass ratio of dichloromethane, n-hexane, and cyclohexane was 1:1:2) to obtain an ionic polymer solid precipitate. The clean ionic polymer solid PFNA-10 was obtained by vacuum drying at 45°C for 72 h. The grafting rate of PFNA-10 was 99.8%, and the EW was 902 g / mol.
[0142]
[0143] (6) 10 mL of the ion polymer solution was cast in an ultra-flat petri dish, dried at 80°C for 12 h, and heat treated at 160°C for 15 min to obtain an ion exchange membrane PEM-200 with an average thickness of 200 μm. The IEC of PEM-200 was 1.11 mmol / g.
[0144] Example 3
[0145] (1) 10 g of the sulfonyl fluoride resin 1 in Example 1 was weighed and swelled in a mixed solvent of 161.2 g of hexafluorobenzene and 20.7 g of dioxane. The swelling process was carried out in a three-necked flask.
[0146] (2) Weigh 14.2 g of 4-fluorobenzenesulfonamide and dissolve it in 28.1 g of DMAc. After it is fully dissolved, pour the functionalization reagent solution into the flask and stir to mix.
[0147] (3) Add 14.6 g of triethylamine to the flask, stir and mix for 10 min, raise the temperature to 80°C, and react under condensation reflux for 36 h.
[0148] (4) After the reaction is completed, the solid crude product is washed alternately with ethyl acetate and acetone, and then poured into 12.4% concentrated hydrochloric acid for acidification at a temperature of 80° C. for 24 hours. The acidified solid product is washed with acetone until the pH value of the washing solution reaches 6.5 to 7.5. The washed solid is dissolved in 142.2 g of DMF, and the insoluble matter is removed by filtration to obtain an ionic polymer solution.
[0149] (5) The ionic polymer solution was poured into 500 mL of a poor solvent (the mass ratio of dichloromethane, n-hexane, and cyclohexane was 1:1:2) to obtain an ionic polymer solid precipitate. The ionic polymer solid PFNA-11 was obtained by vacuum drying at 45°C for 72 h. The grafting rate of PFNA-11 was 84.6% and the EW was 878 g / mol.
[0150] Example 4
[0151] Different from Example 3, the reaction time was 12 h, and a clean ionic polymer solid PFNA-12 was obtained. The grafting rate of PFNA-12 was 52.7%, and the EW was 828 g / mol.
[0152] Example 5
[0153] Different from Example 3, the reaction time was 1 h, and a clean ionic polymer solid PFNA-13 was obtained. The grafting rate of PFNA-13 was 11.3%, and the EW was 763 g / mol.
[0154] Example 6
[0155] (1) 129 g of hexafluorobenzene and 20.7 g of dioxane were added to a flask to obtain a mixed solvent, and 10 g of sulfonyl fluoride resin 2 was added. The mixture was stirred at 50° C. for 2 h to allow the sulfonyl fluoride resin 2 to fully swell.
[0156] (2) 10.0 g of 4-fluorobenzenesulfonamide was dissolved in 28.4 g of anhydrous DMF and added to a flask.
[0157] (3) 4.4 g of triethylamine was added dropwise at 20°C, the temperature was raised to 80°C, and the reaction was stirred for 48 hours.
[0158] (4) After the reaction is completed, the solid product is washed alternately with acetone and ethanol, and then added to a 18.6% hydrochloric acid solution for acidification at a temperature of 60° C. for 24 hours. The acidified solid product is washed with water until the pH value of the washing solution reaches 6.5 to 7.5. The washed solid is dissolved in 110 g of DMSO, and the insoluble matter is filtered out to obtain an ionic polymer solution.
[0159] (5) The ionic polymer solution was poured into 400 mL of a poor solvent (the mass ratio of dichloromethane to acetone was 1:1) to obtain an ionic polymer solid precipitate. The ionic polymer solid PFNA-14 was obtained by vacuum drying at 45°C for 72 h. The grafting rate of PFNA-14 was 99.5% and the EW was 1206 g / mol.
[0160] The structural formula of sulfonyl fluoride resin 2 is:
[0161]
[0162] The structural formula of PFNA-14 is:
[0163]
[0164] Example 7
[0165] (1) 10 g of sulfonyl fluoride resin 3 was weighed and swelled in a mixed solvent of 161.2 g of hexafluorobenzene and 20.7 g of dioxane. The swelling process was carried out in a three-necked flask.
[0166] (2) Weigh 13.5 g of 4-trifluoromethylbenzenesulfonamide and dissolve it in 28.4 g of DMF. After it is fully dissolved, pour the functionalizing agent solution into the flask and stir to mix.
[0167] (3) Add 14.6 g of triethylamine to the flask, stir and mix for 10 min, raise the temperature to 80°C, and react under condensation reflux for 48 h.
[0168] (4) After the reaction is completed, pour out the reaction product. Wash the solid product with butanone, then add it to 6.2% hydrochloric acid and acidify it at 80°C for 24 hours. Wash the acidified solid product with acetone until the pH value of the washing solution reaches 6.5-7.5. Dissolve the washed solid in 200 mL of a water-alcohol mixed solvent (the mass ratio of water, ethanol, and isopropanol is 1:2:2), and filter out the insoluble matter to obtain an ionic polymer solution.
[0169] (5) The ionic polymer solution was poured into 600 mL of a poor solvent (acetone:cyclohexane mass ratio of 8:2) to obtain an ionic polymer solid precipitate. The ionic polymer solid was vacuum dried at 45°C for 72 h to obtain a clean fluorinated polymer solid PFNA-15. The grafting rate of PFNA-15 was 98.9% and the EW was 925 g / mol.
[0170] The structural formula of sulfonyl fluoride resin 3 is:
[0171]
[0172] The structural formula of PFNA-15 is:
[0173]
[0174] Example 8
[0175] Weigh 0.5 g of the PFNA-9 in Example 1 and dissolve it in a mixed solvent (the mass ratio of water, ethanol and n-propanol is 1:2:1) at 80°C to obtain a resin dispersion, cast it in an ultra-flat culture dish, dry it at 60°C for 12 h, and heat treat it at 160°C for 20 min to obtain an ion exchange membrane PEM-9 with an average thickness of 50 μm.
[0176] Example 9
[0177] 10 g of PFNA-10 in Example 2 was weighed and dissolved in 40 g of a water-alcohol mixed solvent (water, ethanol, n-propanol, isopropanol, n-butanol in a mass ratio of 2:1:1:1:1) at 60° C. to obtain a resin dispersion. The dispersion was coated on a release film with a doctor blade, dried at 90° C. for 10 min, and heat treated at 150° C. for 30 min to obtain an ion exchange membrane PEM-10 with an average thickness of 25 μm.
[0178] Example 10
[0179] The difference from Example 9 is that the ionic polymer is PFNA-11 in Example 3, and the ion exchange membrane PEM-11 has an average thickness of 25 μm.
[0180] Embodiment 11
[0181] The difference from Example 9 is that the ionic polymer is PFNA-12 in Example 4, and the ion exchange membrane PEM-12 has an average thickness of 25 μm.
[0182] Example 12
[0183] The difference from Example 9 is that the ionic polymer is PFNA-13 in Example 5, and the ion exchange membrane PEM-13 has an average thickness of 25 μm.
[0184] Embodiment 13
[0185] 1 g of PFNA-14 in Example 6 was weighed and dissolved in 9 g of DMSO at 60° C. to obtain a resin dispersion, which was cast into an ultra-flat culture dish, dried at 100° C. for 24 h, and heat treated at 180° C. for 10 min to obtain an ion exchange membrane PEM-14 with an average thickness of 100 μm.
[0186] Embodiment 14
[0187] 5 g of PFNA-14 in Example 6 was weighed and dissolved in 30 mL of a mixed solvent (water, n-propanol and DMF in a mass ratio of 1:3:1), slit coated on both sides of ePTFE-1, dried at 100°C for 15 min, and heat treated at 160°C for 15 min to obtain an ion exchange membrane PEM-14C with an average thickness of 5 μm. The ion exchange capacity of PEM-14C is 0.52 mmo / g, the tensile strength is 91 MPa, the tensile modulus is 672 MPa, and the conductivity at 90°C and 90% RH is 58 mS / cm.
[0188] Among them, the porous polytetrafluoroethylene membrane (e-PTFE-1) is prepared by the common biaxial stretching method: (A) 75 parts of PTFE powder (Daikin F107) and 25 parts of auxiliary oil (aviation kerosene) are mixed and stirred evenly, and then prepared into a calendered belt containing auxiliary oil after aging, blanking, pushing and extrusion; (B) The calendered belt is dried to obtain a degreased membrane, and the degreased membrane is first stretched in the MD direction and then stretched in the TD direction, and a porous polytetrafluoroethylene membrane is obtained after heat setting. The stretching multiple in the MD direction is 8 times, and the stretching multiple in the TD direction is 30 times. Among them, the mechanical force direction is MD, and the cross-section to the mechanical force direction is TD. The thickness of e-PTFE-1 is 3±1.5μm, the porosity is 78.2%, and the average pore size is 276nm.
[0189] Embodiment 15
[0190] 5 g of PFNA-15 in Example 7 was weighed and dissolved in 20 mL of a hydroalcohol solvent (the mass ratio of water, ethanol and n-propanol was 2:2:1), coated on both sides of the ePTFE-2 with a scraper, dried at 100° C. for 15 min, and heat treated at 160° C. for 15 min to obtain an ion exchange membrane PEM-15 with an average thickness of 12 μm.
[0191] The preparation method of the porous polytetrafluoroethylene membrane (ePTFE-2) is basically the same as that of ePTFE-1, except that the stretching multiple in the MD direction is 7 times and the stretching multiple in the TD direction is 25 times. The thickness of e-PTFE-2 is 7±2μm, the porosity is 77.5%, and the average pore size is 254nm.
[0192] Example 16
[0193] 5 g of PFNA-15 in Example 7 was weighed and dissolved in 20 mL of a water-alcohol solvent (the mass ratio of water, ethanol and n-propanol was 2:2:1), and coated on both sides of the ePTFE-3 with a scraper, dried at 100° C. for 15 min, and heat treated at 160° C. for 15 min to obtain an ion exchange membrane PEM-15C with an average thickness of 40 μm. The ion exchange capacity of PEM-15C is 0.94 mmo / g, the tensile strength is 66.4 MPa, the tensile modulus is 726 MPa, and the conductivity at 90° C. and 90% RH is 128 mS / cm.
[0194] Among them, the preparation method of porous polytetrafluoroethylene membrane (ePTFE-3) is basically the same as that of ePTFE-1, except that the stretching ratio in MD direction is 5.2 times and the stretching ratio in TD direction is 18 times. The thickness of e-PTFE-3 is 25±3μm, the porosity is 76.8%, and the average pore size is 252nm.
[0195] Comparative Example 1
[0196] Weigh 0.5 g of perfluorosulfonic acid resin 4 and dissolve it in a mixed solvent (the mass ratio of water, ethanol and n-propanol is 1:2:1) at 80°C to obtain a resin dispersion, cast it in an ultra-flat culture dish, dry it at 60°C for 12 h, and heat treat it at 160°C for 20 min to obtain an ion exchange membrane D-PEM-9 with an average thickness of 50 μm.
[0197] The EW of perfluorosulfonic acid resin 4 is 980 g / mol, and the structural formula is:
[0198]
[0199] Comparative Example 2
[0200] 10 g of perfluorosulfonic acid resin 1 was weighed and dissolved in 40 g of a water-alcohol mixed solvent (water, ethanol, n-propanol, isopropanol, n-butanol in a mass ratio of 2:1:1:1:1) at 60°C to obtain a resin dispersion. The dispersion was coated on a release film with a doctor blade, dried at 90°C for 10 min, and heat treated at 150°C for 30 min to obtain an ion exchange membrane D-PEM-10 with an average thickness of 25 μm.
[0201] The EW of perfluorosulfonic acid resin 1 is 740 g / mol, and the structural formula is:
[0202]
[0203] Comparative Example 3
[0204] Perfluorosulfonyl imide resin 5 is prepared by free radical copolymerization of perfluorosulfonyl imide vinyl ether monomer and tetrafluoroethylene monomer. Specifically, perfluorosulfonyl imide vinyl ether monomer and tetrafluoroethylene monomer (TFE) are continuously copolymerized in disodium hydrogen phosphate / sodium dihydrogen phosphate buffer using ammonium persulfate (0.3126 g) / sodium bisulfite (0.2838 g) as initiators.
[0205] First, 2.97g of disodium hydrogen phosphate heptahydrate and 0.2838g of sodium dihydrogen phosphate were fully dissolved in 260mL of deionized water after degassing to prepare a first solution; then, 4.169g of perfluorosulfonyl imide vinyl ether monomer was added to the first solution, and the solution was cooled to 8°C under a nitrogen atmosphere to prepare a second solution. The autoclave was evacuated, and the initiator was added to the second solution after being purged with nitrogen three times within 5 minutes; the second solution with the added initiator was degassed with helium for more than 20 minutes; the solution was sucked into a completely evacuated autoclave, and an appropriate amount of degassed deionized water was added so that the volume of the solution was half of that of the reactor. When the reactor temperature reaches 10°C, TFE is added until the pressure reaches 150 psi and the pressure is maintained at 145-150 Pa by adding TFE throughout the process; finally, the filtrate is acidified with 37% hydrochloric acid (200 mL) to obtain a precipitated polymer, the polymer is washed with water until the water is neutral and the pH value is 6.5-7.5, and vacuum dried at 50°C for 24 h to obtain D-PFNA-14F.
[0206] The EW of D-PFNA-14F is 1200 g / mol, and the structural formula is:
[0207]
[0208] Weigh 1 g of D-PFNA-14F and dissolve it in 9 g of DMSO at 60°C to obtain a resin dispersion, cast it in an ultra-flat culture dish, dry it at 100°C for 24 h, and heat treat it at 180°C for 10 min to obtain an ion exchange membrane D-PEM-14F with an average thickness of 100 μm.
[0209] Comparative Example 4
[0210] Different from Example 6, the functionalizing agent is 7.5 g benzenesulfonamide, and the ionic polymer D-PFNA-14 is obtained. The grafting rate of D-PFNA-14 is 99.8%, the EW is 1189 g / mol, and the structural formula is:
[0211]
[0212] Weigh 1 g of D-PFNA-14 and dissolve it in 9 g of DMSO at 60°C to obtain a resin dispersion, cast it in an ultra-flat culture dish, dry it at 100°C for 24 h, and heat treat it at 180°C for 10 min to obtain an ion exchange membrane D-PEM-14 with an average thickness of 100 μm.
[0213] Comparative Example 5
[0214] 5 g of the perfluorosulfonic acid resin 4 in Comparative Example 1 was weighed and dissolved in 20 mL of a hydroalcohol solvent (the mass ratio of water, ethanol and n-propanol was 2:2:1), coated on both sides of the ePTFE-2 with a scraper, dried at 100° C. for 15 min, and heat treated at 160° C. for 15 min to obtain an ion exchange membrane D-PEM-15 with an average thickness of 12 μm.
[0215] The performance tests were conducted on the ion exchange membranes prepared in Examples 8 to 15 and Comparative Examples 1 to 5. The results are shown in Table 4, Table 5 and Table 6, respectively.
[0216] Among them, the test methods for conductivity, EW, IEC, water absorption and mechanical properties refer to GB / T20042.3-2022 "Proton Exchange Membrane Fuel Cell Part 3: Proton Exchange Membrane Test Method".
[0217] Fuel cell polarization curve: The test method refers to GB / T20042.5-2022 "Proton exchange membrane fuel cell Part 5: Membrane electrode test method".
[0218] Free radical resistance of ion exchange membranes and ion polymers: Ion exchange membranes or ion polymers were immersed in Fenton's reagent at 80°C for 8 hours, and the mass loss and conductivity decay before and after immersion were compared. Preparation of Fenton's reagent: 0.1 mL of Fe with a molar concentration of 0.01 mol / L was added to 50 mL of 3% H2O2 solution. 2+ The solution is the Fenton reagent, which is prepared and used immediately. The smaller the mass loss percentage, the better the durability. The smaller the conductivity decay of the ion exchange membrane after Fenton reagent treatment, the better the free radical resistance.
[0219] Table 4 shows the water absorption, tensile strength, tensile modulus and free radical resistance of the ion exchange membranes in Example 8, Example 13, Example 15, Comparative Example 1 and Comparative Examples 3 to 5, and Table 5 shows the conductivity at different relative humidity. The test temperatures of the conductivity are 80°C and 90°C, and the relative humidity is 50% and 80%, respectively. Table 6 shows the IEC, water absorption and conductivity of the ion exchange membranes in Examples 9 to 12 and Comparative Example 2. The test temperatures of the conductivity are 80°C, and the relative humidity is 50% and 80%, respectively.
[0220] Table 4
[0221]
[0222] Table 5
[0223]
[0224]
[0225] Compared with D-PEM-9, PEM-9 has similar IEC, water absorption and free radical resistance, because their EW is similar and both are perfluorinated structures. PEM-9 has higher tensile strength and modulus, because the end group of PFNA-9 is a rigid perfluorophenyl group. The rigid group increases the modulus of the treatment, and the hydrogen bonding formed by the fluorine substituent is beneficial to improve the tensile strength of the material. At different temperatures and humidities, PEM-9 has higher conductivity, which is determined by the strong gas-phase acidity of the sulfonimide group. PEM-9 exhibits better mechanical and electrochemical properties.
[0226] Compared with D-PEM-14F, PEM-14 has similar IEC, water absorption and conductivity under different temperature and humidity. PEM-14 is slightly weaker in free radical resistance than D-PEM-14F because PFNA-14 contains CH structure on the end group, while D-PFNA-14F is a perfluorinated structure. PEM-14 has higher tensile strength and tensile modulus and better mechanical durability. Compared with D-PFNA-14F, the synthesis method of PFNA-14 is simpler and easier to scale up, and its chemical durability and mechanical properties meet the needs of clean energy devices such as fuel cells, flow batteries, and water electrolyzers.
[0227] Compared with D-PEM-14, PEM-14 has similar IEC and water absorption. PEM-14 is superior to D-PEM-14 in mechanical properties, free radical resistance and electrical conductivity under different temperature and humidity. This is because the fluorine substituents on the end groups of PFNA-14 are beneficial to improving the mechanical properties, chemical stability and ion transport properties of the material. The reactivity of the two functionalized reagents is similar, and the cost difference is small. When applied to proton membranes, the core performance of PEM-14 is superior to D-PEM-14, making it a more preferred ion exchange membrane material.
[0228] Compared with D-PEM-15, PEM-15 has the same reinforcement layer and similar water absorption, and the IEC of the former is slightly higher than that of the latter. In terms of electrochemical performance, the conductivity of the two is similar under the conditions of 80°C and 80% RH. When the temperature is increased and the humidity is reduced, PEM-15 shows higher ion transmission capacity. The mechanical properties of PEM-15 are better than those of D-PEM-15, and its free radical resistance is slightly lower than that of D-PEM-15, but it still has good free radical resistance and shows good mechanical durability and chemical durability.
[0229] Table 6
[0230]
[0231]
[0232] The main chain structures of D-PEM-10 and PEM10-13 are consistent, but there are differences in the side chain structures. With the increase of the grafting rate of the sulfonyl imide group, the IEC and water absorption of the ion exchange membrane decrease, and the conductivity at 80°C and 50% RH increases. The relative molecular weight of the sulfonyl imide side chain is higher than that of the sulfonic acid side chain. Therefore, the higher the grafting rate of the sulfonyl imide group, the higher the EW of the ion polymer, and the lower the IEC of the corresponding ion exchange membrane. The reduction of IEC will reduce the water absorption rate. The longer the length of the sulfonyl imide side chain will also reduce the free water absorbed in the material and reduce the water absorption rate of the material. With the increase of the grafting rate of the ion polymer, the conductivity at 80°C and 80% RH first increases and then decreases. This is because both sulfonic acid and sulfonyl imide have excellent ion transmission capabilities at this temperature and humidity. The water absorption rate of D-PEM-10 is too high, resulting in severe swelling, and the concentration of ion transmission groups per unit volume is reduced, which is not conducive to the transmission of ions. PEM-10 has a low water absorption rate, and the number of hydrated ions in the membrane is small, which also limits ion transmission. PEM-11 and PEM-12 have moderate water absorption rates and contain a certain number of sulfonic acid groups and sulfonimide groups, which can form dual ion transmission channels in the ion exchange membrane and have higher conductivity under high temperature and high humidity conditions. By controlling the reaction conditions, ion polymers with different grafting rates can be prepared, and then ion exchange membranes with different properties can be prepared. Appropriate ion polymers and ion exchange membranes can be selected according to specific application requirements.
[0233] Figure 1 This is the infrared spectrum of PEM-9, PEM-10 and D-PEM-14F. Wave number 1050cm -1 Nearby are the characteristic peaks of the SNS group. The three samples mentioned above have peaks at wavenumbers of 1052 cm -1 、1052cm -1 、1055cm -1 The peaks at 1284 cm-1 indicated that they all contained SNS groups, proving that the sulfonimide groups were successfully grafted onto the polymer side chains. The benzene ring had multiple characteristic peaks, including the wave number 1284 cm-1. -1 The peaks of PEM-9 and PEM-10 are the CF vibration peaks of the benzene ring; the wave number is 876cm -1 The PEM-10 peak is the out-of-plane bending vibration peak of the benzene ring CH; wave number 1600-1800cm -1The sawtooth-shaped doublet absorption peaks (belonging to the doublet or group frequency absorption of the CH out-of-plane and C=C in-plane bending vibrations) appearing in PEM-9 and PEM-10 are typical characteristic peaks of substituted benzene.
[0234] Figure 2 The following are SEM images of the cross-section of PEM-15 and D-PEM-15. Both materials have good filling effect in the reinforcement layer.
[0235] Figure 3 The polarization curves of PEM-15 and D-PEM-15 fuel cell cells. At 80°C and 35% RH, the power density of the membrane electrode prepared by PEM-15 reaches 1260mW / cm 2 @0.6V, better than D-PEM-15’s 887mW / cm 2 @0.6V, and has lower internal resistance and better fuel cell single cell performance.
[0236] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0237] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. An ionic polymer, characterized in that Its structural formula is shown in formula (1): In formula (1), a=a positive integer of 0 to 6, b=a positive integer of 2 to 5, x=2 to 10, y=1 to 10000, z×100%≥0.1%; M is hydrogen, lithium, sodium, potassium, rubidium, cesium or other cations, wherein the other cations include at least one of ammonium ion, alkaline earth metal ion, iron ion, vanadium ion, titanium ion, silver ion, cerium ion, zinc ion and manganese ion; R0 is selected from at least one of -OM, -F, -Cl, -Br, -I; R1 is selected from alkylene, fluoroalkylene or direct bond; R2, R3, R4, R5 and R6 are each independently selected from at least one of H, alkyl, cycloalkyl, fluoroalkyl, alkylene, phenyl, phenylene, F, and nitrile, and at least one of them is not H.
2. The ionic polymer according to claim 1, characterized in that The EW of the ionic polymer is 450 to 2000 g / mol.
3. The ionic polymer according to claim 1, characterized in that The terminal structure in the formula (1) At least one of the following structures:
4. The method for preparing an ionic polymer according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) swelling a sulfonyl halide resin in a first organic medium; (2) dispersing a functionalizing agent in a second organic medium to obtain a functionalizing agent solution; (3) mixing the swollen sulfonyl halide resin obtained in step (1) and the functionalizing agent solution obtained in step (2), adding an organic base to form a reaction solution, and performing a nucleophilic substitution reaction to obtain a crude ionic polymer product; (4) washing the crude ion polymer product obtained in step (3) with a third organic medium, adding the crude product solid to an acid solution for acidification to obtain a crude product solid, washing the crude product solid with water and / or a fourth organic medium, and then dispersing the crude product solid in water and / or a fifth organic medium and filtering to obtain an ion polymer solution; (5) drying the ionic polymer solution obtained in step (4) to obtain an ionic polymer solid; or, pouring the ionic polymer solution obtained in step (4) into a poor solvent for precipitation, and drying to obtain an ionic polymer solid.
5. The method for preparing an ionic polymer according to claim 4, characterized in that: In the step (1), the first organic medium comprises at least one of acetonitrile, toluene, xylene, carbitol, dioxane, cyclohexane, hexafluorobenzene, decafluorobiphenyl, hexafluoropropylene trimer, pentafluorophenol, perfluoromethyldecahydronaphthalene or tetrahydrofuran; And / or, in the step (1), the mass ratio of the sulfonyl halide resin to the first organic medium is 1:3-30.
6. The method for preparing an ionic polymer according to claim 4, characterized in that: In the step (2), the functionalizing agent includes a sulfonamide compound, and the sulfonamide compound includes 2-fluorobenzenesulfonamide, 3-fluorobenzenesulfonamide, 4-fluorobenzenesulfonamide, 2,3-difluorobenzenesulfonamide, 2,4-difluorobenzenesulfonamide, 2,5-difluorobenzenesulfonamide, 2,6-difluorobenzenesulfonamide, 3,4-difluorobenzenesulfonamide, 3,5-difluorobenzenesulfonamide, 2,3,4-trifluorobenzenesulfonamide, 2,3,5-trifluorobenzenesulfonamide, 2,4,5-trifluorobenzenesulfonamide, 2,3,6-trifluorobenzenesulfonamide, 2,4,6- trifluorobenzenesulfonamide, 3,4,5-trifluorobenzenesulfonamide, 2,3,5,6-tetrafluorobenzenesulfonamide, pentafluorobenzenesulfonamide, 2-(trifluoromethyl)benzenesulfonamide, 3-(trifluoromethyl)benzenesulfonamide, 4-(trifluoromethyl)benzenesulfonamide, 2,5-bis(trifluoromethyl)benzenesulfonamide, 3,5-bis(trifluoromethyl)benzenesulfonamide, o-methylbenzenesulfonamide, m-methylbenzenesulfonamide, p-methylbenzenesulfonamide, 2,6-dimethylbenzenesulfonamide, 3,5-dimethylbenzenesulfonamide, 2,4,6-trimethylbenzenesulfonamide, 3,4,5-trimethylbenzenesulfonamide Benzenesulfonamide, 2,3,5,6-tetramethylbenzenesulfonamide, 4-ethylbenzenesulfonamide, 4-propylbenzenesulfonamide, 4-tert-butylbenzenesulfonamide, 2,4,6-triisopropylbenzenesulfonamide, naphthalene-2-sulfonamide, 4-methyl-1-naphthalenesulfonamide, 5,6,7,8-tetrahydro-2-naphthalenesulfonamide, 4-biphenylsulfonamide, biphenyl-2-sulfonamide, 4′-fluorobiphenyl-4-sulfonamide, 2-cyanobenzenesulfonamide, 4-cyanobenzenesulfonamide, 2-fluoro-3-methylbenzenesulfonamide, 2-fluoro-4-methylbenzenesulfonamide, 2-fluoro-5-methyl At least one of benzenesulfonamide, 2-fluoro-5-cyanobenzenesulfonamide, 3-cyano-4-fluorobenzenesulfonamide, 4-fluoro-3-(trifluoromethyl)benzenesulfonamide, 4-fluoro-2-(trifluoromethyl)benzenesulfonamide, 2-fluoro-5-(trifluoromethyl)benzenesulfonamide, o-trifluoromethylbenzylsulfonamide, 3-(trifluoromethyl)benzylsulfonamide, 4-methylbenzylsulfonamide, 2-(1-naphthyl)ethanesulfonamide, (3-methylphenyl)methanesulfonamide, 4-fluorophenylmethanesulfonamide, (3,5-difluorophenyl)methanesulfonamide, and 2-phenyl-ethanesulfonamide; And / or, the second organic medium includes at least one of acetonitrile, cyclohexane, toluene, xylene, carbitol, dioxane, DMSO, DMF, DMAc, tetramethylene sulfoxide, hexamethylphosphoramide, N-methylpyrrolidone or tetrahydrofuran.
7. The method for preparing an ionic polymer according to claim 4, characterized in that: In the step (3), the organic base includes at least one of an organic amine containing no nitrogen heterocycle and a nitrogen heterocyclic compound; the organic amine containing no nitrogen heterocycle includes C1 to C 20 Alkyl and / or C6~C 20 At least one of the organic amines containing no nitrogen heterocyclic ring substituted with an aromatic group; the nitrogen heterocyclic compound includes C1 to C 20 Alkyl and / or C6~C 20 At least one of pyridine, imidazole, pyrrole, piperidine or piperazine substituted with an aromatic group; And / or, in the step (3), the mass ratio of the sulfonyl halide resin, the functionalizing agent, and the organic base in the reaction solution is 100:1-400:1-600; And / or, in the step (3), the temperature of the nucleophilic substitution reaction is 50 to 180° C., the pressure of the nucleophilic substitution reaction is 0.1 to 10 MPa, and the time of the nucleophilic substitution reaction is 1 to 120 h.
8. The method for preparing an ionic polymer according to claim 4, characterized in that: In the step (4), the third organic medium comprises at least one of aliphatic alcohols, lipids, fatty acids, ketones, tetrahydrofuran, cyclohexane, aromatic hydrocarbons or halogenated hydrocarbons; And / or, in step (4), the acid solution comprises at least one of a sulfuric acid solution, a nitric acid solution, a phosphoric acid solution or a hydrochloric acid solution; And / or, in the step (4), the temperature of the acidification treatment is 20 to 100° C., and the time of the acidification treatment is 1 to 48 hours; and / or, in step (4), the fourth organic medium comprises at least one of fatty alcohols, lipids, fatty acids, ketones or tetrahydrofuran; And / or, in the step (4), the fifth organic medium comprises at least one of aliphatic alcohol, fatty acid, ethylene glycol, propylene glycol, glycerol, DMF, DMSO, DMAc, tetramethylene sulfoxide, tetrahydrofuran, hexamethylphosphoramide, and NMP; And / or, in step (4), the solid content of the ionic polymer solution is 0.5% to 40%.
9. The method for preparing an ionic polymer according to claim 4, characterized in that: In the step (5), the drying method is freeze drying, forced air drying or vacuum drying; And / or, in step (5), the volume of the poor solvent is 2 to 5 times that of the ionic polymer solution; And / or, in step (5), the poor solvent includes at least one of lipids, aromatic hydrocarbons, alkanes, ketones, and halogenated hydrocarbons.
10. Use of the ionic polymer according to any one of claims 1 to 3 or the ionic polymer prepared by the preparation method according to any one of claims 4 to 9 in ion exchange membranes.
11. An ion exchange membrane, characterized in that: The invention comprises the ionic polymer described in any one of claims 1 to 3 or the ionic polymer prepared by the preparation method described in any one of claims 4 to 9.
12. The ion exchange membrane according to claim 11, characterized in that Also included are reinforcement films.
13. Use of the ion exchange membrane according to claim 11 or 12 in batteries, chlor-alkali industry, water electrolysis hydrogen production, capacitors, electrodialysis, sensors, desalination membranes, ultrafiltration membranes, microfiltration membranes, fabrics, and protective equipment.
